KEPENTINGAN INDONESIA MEMBERLAKUKAN PENGENAAN BEA MASUK YANG TINGGI UNTUK PRODUK MINUMAN BERALKOHOL (MINOL) DI ASEAN FREE TRADE AREA (AFTA) TAHUN 2015-2018 - Putri, Siska Yama; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research describes about the interest of Indonesia to impose a high import duty on alcohol beverage products in the ASEAN Free Trade Area (AFTA) in 2015-2018. ASEAN member countries agreed to form the ASEAN Free Trade Area. AFTA was formed to form a trade-free region in order to increase the economic capacity of the ASEAN region.The study was prepared using the protection theory by Friedrich List, concept national interest, the mercantilism perspective, which is then supported by nation-state analysis level. The methodology using a qualitative method and collecting the data using a library research literature This research shows Indonesia's interest in alcoholic beverages for its national interest, namely protecting its people from the negative effects of alcoholic beverages and state revenues from import duties on alcoholic beverages. Indonesia needs an import duty of 150%. Keywords: interest, alcohol, import duty, ASEAN Free Trade Area (AFTA)